Cancer and Immunomodulators in Inflammatory Bowel Diseases. Issue 3 (March 2015) - Biancone, Livia; Onali, Sara; Petruzziello, Carmelina; Calabrese, Emma; Pallone, Francesco
Abstract : Abstract: The widespread use of thiopurines and anti-tumor necrosis factors (TNFs) in inflammatory bowel disease (IBD) is a rising concern regarding their potential cancer risk. MEDLINE, EMBASE, and the Cochrane Library database were searched for articles regarding immunomodulators anti-TNF agents in IBD, hematologic malignancies, and solid tumors. Current evidences support that thiopurines and anti-TNFs used alone or in combination do not increase the overall cancer risk in IBD. Thiopurines use, with or without anti-TNFs, is associated with an increased risk of lymphoma, particularly non-Hodgkin lymphoma, in Crohn's disease. Combined treatment significantly increases the risk of a rare hepatosplenic T-cell lymphoma, particularly in young male patients with Crohn's disease. An increased risk of nonmelanotic skin cancer is also observed when using thiopurines in IBD, whereas a slightly increased risk of melanoma is observed when using anti-TNFs. The role played by immunomodulators in the development of other cancer types (i.e., urinary) as also by the severity of IBD is under investigation. Although the incidence of specific malignancies (lymphoma, skin cancers) seems to be increased by immunomodulators, their absolute number is low. As thiopurines and anti-TNFs are highly effective in IBD, current evidences support that in appropriate hands, their benefits overwhelm the cancer risk. However, a careful selection of both patients and timing of treatment is mandatory, particularly in young male patients with Crohn's disease. Immunomodulators should therefore be handled by experienced and dedicated gastroenterologists who aware of the potential, although low, cancer risk associated with their use in patients with IBD. Abstract : Article first published online 24 December 2014.